1991
DOI: 10.1159/000147091
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Innervation of the Rat Knee Joint Articular Capsule and Ligaments

Abstract: In spite of the practical importance of having a detailed knowledge of knee joint innervation to understand the pathophysiologic aspects, little information is now available concerning the density and pattern of the nerve fibres which are distributed to it. The present study has been designed to investigate the density and distribution of nerve fibres and receptor corpuscles in the knee joint articular capsule, cruciate and collateral ligaments in the rat, using the acetylcholinesterase (AChE) histochemical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 7 publications
1
11
1
1
Order By: Relevance
“…8,9,[23][24][25][26] By using the modified gold chloride histologic method, the present study has shown 4 types of nerve endings resembling those described by Freeman and Wyke. 15 It has been shown that different nerve endings are supplied by nerve fibers of different calibers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…8,9,[23][24][25][26] By using the modified gold chloride histologic method, the present study has shown 4 types of nerve endings resembling those described by Freeman and Wyke. 15 It has been shown that different nerve endings are supplied by nerve fibers of different calibers.…”
Section: Discussionsupporting
confidence: 59%
“…3,[8][9][10] It is believed that the articular innervation is important in active protection of the articular tissues by reflex control of the appropriate musculature. 11 The most comprehensive account of the nerve supply of the human knee was probably by Gardner.…”
mentioning
confidence: 99%
“…Knee joints are strongly innervated by both sympathetic and sensory nerves, with nociceptors present throughout most of the joint, including the capsule, ligaments, menisci and bones 98,99 . During inflammatory states of the joint, nociceptors become spontaneously active and sensitized to mechanical stimuli 100,101 .…”
Section: Actions Of Neuropeptides On Immune Cellsmentioning
confidence: 99%
“…는 전방십자인대의 기 동물을 이용한 십자 인대의 감각신경섬유에 대한 동물적 연구는 종종 보고되고 있으나 [6][7][8][9][10] , 인체의 전방십자인대의 감 각신경섬유에 대한 연구는 전방 십자인대 조직의 습득이 어렵 기 때문에 드물다 11,12) . 그리고, 보고된 결과를 살펴 보면, Zimny 등 (Table 1).…”
unclassified